APPLICATION OF SELECTIVE ARTERIAL EMBOLIZATION FOR TREATMENT OF BENIGN PROSTATIC HYPERPLASIA IN PATIENTS WITH HIGH OPERATIVE RISK - Golovko, S.V.; Kobirnichenko, A.A.; Savytskyi, O.F.; Troyitskyi, I.L. (World of Medicine and Biology, 2018)
The choice of method of treatment of benign prostatic hyperplasia (BPH) in elderly patients with high operative risk is one of the pressing issues of modern urology. Selective arterial embolization (SAE) of the prostate – is a new method of treating lower urinary tract symptoms caused by benign prostatic hyperplasia. The article presents preliminary experience of performing this procedure in a group of 21 patients with high operative risk, describes indications, criteria of patient selection, technique of the procedure, results and prospects of utilizing this method in the clinical practice.